2007
DOI: 10.1088/0953-8984/19/35/356212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of La substitution for Gd in the ionic conductivity and oxygen dynamics of fluorite-type Gd2Zr2O7

Abstract: We have prepared different compositions in the Gd 2−y La y Zr 2 O 7 solid solution by mechanically milling stoichiometric mixtures of the corresponding oxides. Irrespective of their lanthanum content, as-prepared powder samples consist of single-phase anion-deficient fluorite materials, although the long-range ordering of cations and anion vacancies characteristic of pyrochlores was observed for y 0.4 after post-milling thermal treatments at 1200 • C. Ionic conductivity was found to be thermally activated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Enormous amounts of efforts were found in the literature to improve electrical conductivity of oxide electrolyte materials [7][8][9][10]. In recent years, new rareearth zirconates with various ionic radius ratios of r(Ln 3+ )/r(Zr 4+ ) are of considerable scientific interest [11][12][13][14]. Mandal et al [11] found that a significant increase in electrical conductivity was obtained at 622-696 K by properly doping at the Gd site with isovalent rare-earth cations like Nd in Gd 2 Zr 2 O 7 ceramic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enormous amounts of efforts were found in the literature to improve electrical conductivity of oxide electrolyte materials [7][8][9][10]. In recent years, new rareearth zirconates with various ionic radius ratios of r(Ln 3+ )/r(Zr 4+ ) are of considerable scientific interest [11][12][13][14]. Mandal et al [11] found that a significant increase in electrical conductivity was obtained at 622-696 K by properly doping at the Gd site with isovalent rare-earth cations like Nd in Gd 2 Zr 2 O 7 ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…Mandal et al [11] found that a significant increase in electrical conductivity was obtained at 622-696 K by properly doping at the Gd site with isovalent rare-earth cations like Nd in Gd 2 Zr 2 O 7 ceramic. Diaz-Guillen et al [12,13] metric elemental oxides, and found that electrical conductivity of (Gd 1 − x La x )Zr 2 O 7 (0 ≤ x ≤ 0.4) ceramics was almost La-content independent in the temperature range of 773-1023 K. The conductivity of pyrochlore-type Sm 2 Zr 2 O 7 was comparable to those of other good conductors such as yttria-stabilized zirconia in lowtemperature regions [3]. (Sm 1 − x Gd x ) 2 Zr 2 O 7 (0 ≤ x ≤ 1.0) ceramics were synthesized by pressureless-sintering method, and the highest electrical conductivity was obtained for SmGdZr 2 O 7 in the temperature range of 623-873 K [14].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 8 mol-% Y 2 O 3 -ZrO 2 (YSZ) is used as a solid electrolyte in conventional SOFCs, while anode and cathode materials are Ni-YSZ cermets and La 1-x Sr x MnO 3 oxide, respectively [4][5][6]. However, when SOFCs are operated at high temperatures for a long time, unwanted reactions at the cathode/electrolyte interface will generate insulating zirconates (La 2 Zr 2 O 7 and SrZrO 3 ), which may have a detrimental effect on SOFCs performance [7,8]. Pyrochlore oxides of A 2 Zr 2 O 7 -type (A = lanthanide) structure show excellent electrical properties owing to high compositional diversity, structural flexibility and intrinsic concentration of oxygen vacancies [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The dual Yb+Gd intermix doping causes a distinctly enhanced total conductivity as compared to unmodified Nd 2 ) [7,8,[18][19][20]. Díaz-Guillén et al [7,8] found that electrical conductivity of Gd 2-x La x Zr 2 O 7 (0 ≤ x ≤ 1.0) ceramics was almost La-content independent in the temperature range of 773-1,023 K. A significant increase in electrical conductivity is found by suitable substitution of isovalent rare-earth cations like Nd at the Gd site in Gd 2 Zr 2 O 7 from 622 to 696 K [18]. For (Nd 1-x Yb x ) 2 Zr 2 O 7 (0 ≤ x ≤ 1.0) ceramics, electrical conductivity of pyrochlore-type materials is clearly higher than that of defect fluorite-type materials in the temperature range of 723-1,173 K [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the family of pyrochlore-type compounds, Gd 2 Zr 2 O 7 had the highest intrinsic ionic conductivity (10 −3 S cm −1 at 1000 K) at the intermediate temperature as compared with commercially used electrolytes [11]. During the past decades, Gd 2 Zr 2 O 7 doped with different cations has been widely investigated as potential electrolyte materials for intermediate temperature SOFCs [12][13][14][15][16][17][18]. (Gd 0.5 Nd 0.5 ) 2 Zr 2 O 7 exhibited a significant enhancement in ionic conductivity at 622-696 K as compared with pure Gd 2 Zr 2 O 7 [12].…”
Section: Introductionmentioning
confidence: 99%